Degradation of Beryllium Reflector Properties on the IRT-T Reactor; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Naymushin A. G. Artem Georgievich; Chertkov Yu. B. Yuri Borisovich; Varlachev V. A. Valery Aleksandrovich; Anikin M. N. Mikhail Nikolaevich; Chyuykina A.; Ermakova Ya. V. Yanina Viktorovna (Nuclear Engineering and Fuel Cycles, 2015)
Title screen